2017
DOI: 10.1080/15384101.2016.1260210
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of X-box binding protein 1 in NADPH oxidase 4-triggered cardiac hypertrophy is mediated by receptor interacting protein kinase 1

Abstract: NADPH oxidase 4 (NOX4) and the NOX4-related redox signaling are implicated in cardiac hypertrophy. NOX4 is interrelated with endoplasmic reticulum stress (ERS). Spliced X-box binding protein 1 (Xbp1s) is a key mediator of ERS while its role in cardiac hypertrophy is still poorly understood. Recently, receptor interacting protein kinase 1(RIPK1) has been increasingly reported to be associated with ERS. Therefore, we aimed to test the hypothesis that Xbp1s mediates NOX4-triggered cardiac hypertrophy via RIPK1 si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 68 publications
0
10
1
Order By: Relevance
“…Firstly, we evaluated the change of Mfn2 expression in TAC rats compared with that in sham-operated rats. Echocardiography indicators and HE staining suggested that cardiac hypertrophy is induced by the TAC model successfully in our previous papers [11, 18]. As shown in Figure 1(a), the left ventricular weight to body weight (HW/BW) (mg/g) ratio also implied that cardiac hypertrophy was induced in TAC models.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…Firstly, we evaluated the change of Mfn2 expression in TAC rats compared with that in sham-operated rats. Echocardiography indicators and HE staining suggested that cardiac hypertrophy is induced by the TAC model successfully in our previous papers [11, 18]. As shown in Figure 1(a), the left ventricular weight to body weight (HW/BW) (mg/g) ratio also implied that cardiac hypertrophy was induced in TAC models.…”
Section: Resultsmentioning
confidence: 56%
“…Intracellular ROS production was determined by oxidative conversion of cell-permeable 20,70-dichlorofluorescein diacetate (H2DCFDA) (Sigma-Aldrich) to fluorescent dichlorofluorescein [11]. Cardiac fibroblasts were washed with serum-free DMEM and incubated with H2DCFDA (10 mM) for 60 min at 37°C in an incubator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data indicated that the interaction of UnAG with SIRT1 might play a role in coordinating necroptosis during pressure-induced tissue injury, suggesting that SIRT1 might be able to serve as the potential molecular target for further unraveling the pathogenesis of pressure ulcers as well as the myoprotective effect of UnAG in pressure ulcers. Chen et al ( 2017 ) revealed recently that NADPH oxidase 4 (NOX4) increased the expression of RIPK1 and simultaneously activated nuclear factor kappa B (NF-kB) via increased phosphorylation of p65 subunit of NF-kB, in the heart tissue of transverse aortic constriction rats. Notably, gene silencing of NOX4 by specific siRNA effectively opposed the upregulation of RIPK1 and phosphorylation of p65 subunit of NF-kB, suggesting that NOX4 might be required for the activation of necroptosis and NF-kB signaling pathways (Chen et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ( 2017 ) revealed recently that NADPH oxidase 4 (NOX4) increased the expression of RIPK1 and simultaneously activated nuclear factor kappa B (NF-kB) via increased phosphorylation of p65 subunit of NF-kB, in the heart tissue of transverse aortic constriction rats. Notably, gene silencing of NOX4 by specific siRNA effectively opposed the upregulation of RIPK1 and phosphorylation of p65 subunit of NF-kB, suggesting that NOX4 might be required for the activation of necroptosis and NF-kB signaling pathways (Chen et al, 2017 ). Resveratrol, the potent SIRT1 agonist, suppressed NOX4 upregulation in the muscle of dystrophin-deficient mice, whereas SIRT1 knockdown in cultured C2C12 myoblasts resulted in NOX4 protein upregulation (Hori et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%